Electrical design guide for commercial buildings - Clark, William II H. (New York : McGraw Hill Education, 1998)
Shows you step by step how to organize, layout and circuit, and complete the design of electrical power and telephone/communications systems for commercial and industrial buildings. This guide lets you to submit lower bids, foster greater client satisfaction, and encounter fewer problems during construction.
The Fundamentals of Electricity. Electrical Circuits. Phase Diagrams. Power Circuiting. Signals Circuiting. Lighting and Circuiting. Power Distribution System. Designing the Visual Environment. HVAC Equipment. Motors. Transformers. Estimating. Computer Applications. Value Engineering. Load Control and Harmonics. Special Applications. Designing in CAD Programs. Short Specifications. Electrical Checklist. Designing for Conservation. The Production Process.
Includes index.
Keywords: COMMERCIAL BUILDINGS